هێڵە گشتییەکانی شێوازی گێڕانەوە لە دەقی شانۆیی (مامەیارە) دا - حسێن, عطا رشید (Sulaimani Journal for Humanities, 2021)
The present study entitled (The General Outlines of the Narrative Style in the Dramatic Text of MAMA YARA) is a stylistic study and an attempt to identify and explore all the artistic styles underlying the structure of the text in question in terms of title, language, characters, events and plot, time, and place. The study is made up of an introduction and two main sections as well as the findings, conclusions, and the references. The first section covers the theoretical part which includes highlighting the following points: the concept and definition of style, the main principles of style, the modules of the narrative style, the key principles and elements of the narrative style in the title, language, characters, events and plots, place, and time. The second part deals with the practical aspect of the study where the dramatic text of MAMA YARA is closely analyzed from the perspective of the main principles and elements of the narrative in terms of title, language, character, events, place and time.